BFP Niger WP2: Water availability and access - Mahé, Gil; Liénou, Gaston; Adeaga, Olusegun (2009)
The West African drought has now been lasting for more than 30 years. It has tragic consequences in the Sahel countries, such as desertification. This drought, which is notably characterized by a decrease of rainfall, global surface-water flows and by a change in the rainy season characteristics, contributes to reduce the water availability in the Niger River Basin. This climate shift must be born in mind if one wants to understand the present hydrology and water uses in the basin.